Preparation and Characterization of Silicon-Metal Fluoride Reactive Composites - Siva Kumar Valluri; Mirko Schoenitz; Edward Dreizin (Nanomaterials, 2020)
Fuel-rich composite powders combining elemental Si with the metal fluoride oxidizers BiF3 and CoF2 were prepared by arrested reactive milling. Reactivity of the composite powders was assessed using thermoanalytical measurements in both inert (Ar) and oxidizing (Ar/O2) environments. Powders were ignited using an electrically heated filament; particle combustion experiments were performed in room air using a CO2 laser as an ignition source. Both composites showed accelerated oxidation of Si when heated in oxidizing environments and ignited readily using the heated filament. Elemental Si, used as a reference, did not exhibit appreciable oxidation when heated under the same conditions and could not be ignited using either a heated filament or laser. Lower-temperature Si fluoride formation and oxidation were observed for the composites with BiF3; respectively, the ignition temperature for these composite powders was also lower. Particle combustion experiments were successful with the Si/BiF3 composite. The statistical distribution of the measured particle burn times was correlated with the measured particle size distribution to establish the effect of particle sizes on their burn times. The measured burn times were close to those measured for similar composites with Al and B serving as fuels.